What Do We Know about Global Income Inequality? - Anand, S; Segal, P (American Economic Association, 2008)
In this paper, we review the recent literature on global interpersonal income inequality. While all estimates agree that the level is very high, with a Gini of between 0.630 and 0.686 in the 1990s, there is no consensus regarding the direction of change. We discuss methodological issues, including the use of national accounts versus survey-based estimates of mean income (or consumption) and the choice of purchasing power parity exchange rates. Findings of a rise or fall in global income inequality are not robust across different estimation methods and datasets. Given the diversity of estimates and various sources of uncertainty, including gaps and errors in the underlying data, we conclude there is insufficient evidence to determine the direction of change in global interpersonal inequality in recent decades.